Post harvest management guide for common beans: A guide for farmers and extension - Waswa, Boaz; Nchanji, Eileen; Karanja, David; Rubyogo, Jean Claude (2024)
A third of all food produced for human consumption is lost or wasted. The losses and waste occur from the farm to the fork along the food value chain. Post-harvest losses have significant impacts on food and nutrition security, health, and finances for both consumers and farmers, particularly affecting women who manage post-harvest activities. This guide seeks to enhance understanding of the post-harvest management in beans for better decision making. The target beneficiaries of this guide are farmers, extension officers, collection point managers and trainers. The manuals content is designed to address the specific needs and challenges faced by farmers ensuring that they can effectively apply principles of post-harvest loss management, leading to reduced loss, improved food and nutrition security, better incomes, and improved livelihoods